Haematoma and abscess after neuraxial anaesthesia: a review of 647 cases. (April 2018) - Bos, E.M.E.; Haumann, J.; de Quelerij, M.; Vandertop, W.P.; Kalkman, C.J.; Hollmann, M.W.; Lirk, P.
Abstract: Although rare, spinal haematoma and abscess after central neuraxial blocks may cause severe permanent neurological injury. Optimal treatment and outcome remain unclear. In order to identify possible predisposing patient characteristics and describe the ensuing clinical course, we searched Medline, Embase, and the Cochrane Library for reports of spinal haematomas and abscesses associated with central neuraxial blocks. Extracted data included patient characteristics, symptoms, treatment, and outcome. We analysed 409 reports, including 647 patients (387 patients with spinal haematoma and 260 patients with spinal abscess). Spinal haematoma and abscess occurred predominantly after epidural anaesthesia (58% and 83%, respectively). Neurological recovery was correlated with the severity of initial neurological deficit. When decompression of spinal haematoma was delayed for >12 h after clinical diagnosis, neurological outcome was worse compared with earlier decompression (odds ratio 4.5, 95% confidence interval 2.1–9.9, P< 0.001, n =163). After spinal haematoma, 47% of published patients had full recovery, 28% had partial recovery, and in 25% no recovery was observed. Good outcome after conservative management was observed in patients with mild symptoms or with spontaneous recovery during the diagnostic and therapeutic workup. After spinal abscess, 68% of reported patients recovered fully, 21% showed partial recovery, and no recovery was reported in 11%. Persistent neurological symptoms after spinal haematoma and abscess are common and correlate with the severity of initial neurological deficit. Neurological outcome seems worse when decompressive surgery of haematoma is delayed. Notwithstanding the considerable risk of selection bias and publication bias, conservative management may be feasible in patients with mild symptoms or spontaneous recovery.